2003
DOI: 10.1002/ajhb.10158
|View full text |Cite
|
Sign up to set email alerts
|

Influence of some anthropometric parameters on the risk of development of distal complications after mastectomy carried out because of breast carcinoma

Abstract: The analysis included 46 women after radical breast amputation because of cancer with which lymphoedema occurred in the upper limb, as well as 51 women in whom no lymphoedema occurred during the period of the observation. Both groups were subjected to a comparative analysis as for height, body mass, and weight-height indexes: BMI, Quetelet, Rohrer, and Pignet-Verwaeck. The results show that women with high body mass, obesity (BMI > 30.0), and high values of the Quetelet (>370), Rohrer (>1.59), and Pignet-Verwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…The third class consists of patient and clinicalrelated factors such as age, BMI, infection, and excessive use of extremity [1,[22][23][24]. In the literature, a high BMI is a risk factor for BCRL and the severity (high stage and grade) of lymphedema [11,25,26]. In this study, our BCRL patient groups' mean BMI index was over 30 kg/m 2 in all three groups.…”
Section: Discussionmentioning
confidence: 92%
“…The third class consists of patient and clinicalrelated factors such as age, BMI, infection, and excessive use of extremity [1,[22][23][24]. In the literature, a high BMI is a risk factor for BCRL and the severity (high stage and grade) of lymphedema [11,25,26]. In this study, our BCRL patient groups' mean BMI index was over 30 kg/m 2 in all three groups.…”
Section: Discussionmentioning
confidence: 92%
“…A large number of women after mastectomy complain of increased back pain a few months to years after mastectomy [8,9]. The studies by Rostkowska et al have shown a statistically significant disturbance of proper body posture in women after mastectomy [10].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…18,22,66,[70][71][72][73][74] A 20-year retrospective study showed that weight gain since treatment for breast cancer was a stronger predictor of BCRL than being overweight at diagnosis, 23 however determining causation was precluded by the study design.…”
Section: Obesity (High Bmi)mentioning
confidence: 99%